Integrating project-based learning and digital flipbook media to improve students’ learning motivation in Pancasila education - Anton Rio Hasan (Jurnal Inovasi Guru Indonesia, 2026)
Background: Learning motivation plays a crucial role in achieving meaningful outcomes in Pancasila Education, which emphasizes active participation and value internalization. However, conventional teacher-centered instruction often limits students’ engagement and intrinsic interest. Integrating Project-Based Learning (PjBL) with digital flipbook media offers a potential strategy to create interactive, contextual, and student-centered learning experiences. Objective: This study aimed to examine the effect of integrating Project-Based Learning and digital flipbook media on students’ learning motivation in Pancasila Education at the junior high school level. Methods: A quasi-experimental design with a non-equivalent control group pretest–posttest approach was employed. The participants consisted of 64 Grade VIII students divided into an experimental group (n = 32) and a control group (n = 32). The experimental group received instruction through Project-Based Learning integrated with digital flipbook media, while the control group received conventional instruction. Learning motivation was measured using a validated Likert-scale questionnaire administered before and after the intervention. Data were analyzed using descriptive statistics and independent and paired samples t-tests at a significance level of 0.05. Results: The findings revealed a significant increase in learning motivation in the experimental group compared to the control group. The experimental group demonstrated a higher mean gain score, indicating that the integration of Project-Based Learning and digital flipbook media effectively enhanced students’ engagement, confidence, and interest in learning Pancasila Education. Conclusion: The integration of Project-Based Learning and digital flipbook media significantly improves students’ learning motivation in Pancasila Education. This combined approach provides a meaningful and interactive learning environment that supports active participation and value internalization.